2017
DOI: 10.1002/jmv.24935
|View full text |Cite
|
Sign up to set email alerts
|

Viral etiology of sporadic cases of parotitis among children in Korea during 2013‐2014

Abstract: Recent years have seen a high incidence of mumps, which is generally diagnosed based on clinical features, especially parotitis, without laboratory confirmation in Korea. To better understand the epidemiology of mumps in Korean children, we investigated sporadic suspected mumps cases with parotitis. In total, 237 buccal swabs or throat swabs collected from children with parotitis who had been clinically diagnosed with mumps were tested using real-time PCR for the detection of six viruses (Epstein-Barr virus, H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 26 publications
1
10
0
3
Order By: Relevance
“…La lista incluye también inflamación glandular secundaria al síndrome de Sjoegren 11,12 . En un estudio prospectivo infantil con casos esporádicos, el uso de la RPC permitió identificar al virus Epstein Barr como el agente más frecuente de parotiditis, secundado por herpesvirus 6 y en tercer lugar por el virus parotídeo 14 .…”
Section: Discussionunclassified
“…La lista incluye también inflamación glandular secundaria al síndrome de Sjoegren 11,12 . En un estudio prospectivo infantil con casos esporádicos, el uso de la RPC permitió identificar al virus Epstein Barr como el agente más frecuente de parotiditis, secundado por herpesvirus 6 y en tercer lugar por el virus parotídeo 14 .…”
Section: Discussionunclassified
“…According to a recent review, the method of determining ADA values and establishing cut-off points adapted to regions with a high TB rate has a high discriminatory power; in contrast, in low-incidence regions, it would have a high negative predictive value. 2 The main disputable factor is the determination of the cut-off point which enables differentiation of TB from other processes, and varies widely according to the following parameters: (1) the prevalence of TB in the geographical area studied; (2) the age of the patients, as in patients over 55, the cut-off point would drop to 26 IU/l, while in the under-55s it would rise to 72 IU/l, 3 and (3) the number of cases studied. In a study of 2413 cases of pleural effusion duly classified according to aetiology and with a mean age of 65, the mean cut-off point was set at 28.26 IU.…”
Section: Uso De Adenosin Deaminasa Como Indicador Para Seleccionar Límentioning
confidence: 99%
“…To date, only two cases of parotitis have been reported associated with bocavirus infection, one of which being a coinfection with PIV 3. 1,2 These two cases were detected in two prospective studies that surveyed the frequency of several viruses in sporadic parotitis in Korea and U.S.A. The authors observed an incidence of HBoV infection of 0.4-1% in their studied cases.…”
mentioning
confidence: 95%
“…Nowadays the parotitis cases are usually related to other viral infections in countries with high vaccination coverage. 1,2 Although Epstein Barr virus (EBV) has been recognized as the most frequently detected microorganism, other respiratory viruses such as parainfluenza virus (PIV) or adenovirus 1 have been described associated with parotitis.…”
mentioning
confidence: 99%